Chewing lice (Insecta: Phthiraptera) from parrots and parakeets of the genera Cyanoliseus and Enicognathus in Chile and Argentina, with descriptions of a new species - Cicchino, Armando; González-Acuña, Daniel (Zootaxa, 2009)
The following three species of parrots: Enicognathus leptorhynchus (King) (Choroy = Slender-billed Parakeet), E. ferrugineus (-Müller) (Cachaña = Austral Parakeet) and Cyanoliseus patagonus (Vieillot) (Tricahue or Barranquero Parrot = Burrowing Parrot) from Southern Chile and Argentina were examined for chewing lice. Four louse species were found: Psittacobrossus patagoni Price and Beer and Heteromenopon macrurum (Eichler) ex the Austral Parakeet, Paragoniocotes meridionalis Guimarães, H. macrurum and P. patagoni ex the Burrowing Parrot, and H. macrurum and a new species of Paragoniocotes Cummings ex the Slender-billed Parakeet and the Austral Parakeet. P. meriodionalis is a new record for Chilean fauna, and E. leptorhynchus is a new host for H. macrurum. Paragoniocotes enicognathidis n. sp. is described and illustrated, discussing the morphological affinities with its close relatives.